The touristic ancient monuments in Bukhara - Mukhammadaminova, Soliha Ziyodullo qizi (Science and Education, 2024)
This article provides information about historical places in Bukhara. Such as Ismoil Samoni Mausoleum, Magoki-Attori Mosque, Mausoleum of Chashmai-Ayyub, Ulugbek Madrasah, Poikalon Architectural Ensemble, Kalon Mosque, Kukaldosh Madrasah, Lab-I Hauz Complex, Mir-i-Arab Madrasah, Kalyan Minaret, Bahoutdin Architectural Complex, Char Minar, Khanaqah of Nodir Devonbegi, Bukhara Prison, Mosque of Mir Sayyid Ali Hamadani, Shirbudun Palace.